Hubungan Interaksi Sosial dengan Tingkat Kemandirian dalam Pemenuhan Activity Of Daily Living pada Lansia - Dita Fadhila; Didi Kurniawan; Fathra Annis Nauli (Jurnal Vokasi Keperawatan (JVK), 2022)
The ultimate stage of human existence is old age, which causes physical and mental changes. These changes make it difficult for the elderly to adapt to their surroundings and restrict social interaction. Poor social connection has an impact on independence in daily life tasks. The purpose of this study is to establish a relationship between social interaction and the degree of independence in performing daily life tasks. This study employs a correlational descriptive methodology with a cross-sectional approach, implemented in the working area of ​​the Payung Sekaki public Health Center from February to July 2022. Purposive sampling was used to choose 92 respondents depending on inclusion criteria. The measuring instrument utilised is a social interaction questionnaire with r findings (cronbach's alpha) of 0.941 and an activity of daily life instrumental with a correlation value (r) of 0.400. There is a significant link with a p value of 0.000 between the two variables. The more social interacti The ultimate stage of human existence is old age, which causes physical and mental changes. These changes make it difficult for the elderly to adapt to their surroundings and restrict social interaction. Poor social connection has an impact on independence in daily life tasks. The purpose of this study is to establish a relationship between social interaction and the degree of independence in performing daily life tasks. This study employs a correlational descriptive methodology with a cross-sectional approach, implemented in the working area of ​​the Payung Sekaki public Health Center from February to July 2022. Purposive sampling was used to choose 92 respondents depending on inclusion criteria. The measuring instrument utilised is a social interaction questionnaire with r findings (cronbach's alpha) of 0.941 and an activity of daily life instrumental with a correlation value (r) of 0.400. There is a significant link with a p value of 0.000 between the two variables. The more social interaction the elderly have, the more independent the elderly in fulfilling the Activity of Daily Living in the elderly. This study suggests that the elderly remain active in social interactions and remain independent in carrying out daily activities if the conditions are supportive. on the elderly have, the more independent the elderly in fulfilling the Activity of Daily Living in the elderly. This study suggests that the elderly remain active in social interactions and remain independent in carrying out daily activities if the conditions are supportive.